First report of an Escherichia coli from Lebanon carrying an OXA-181 carbapenemase resistance determinant - Tokajian, Sima (2018)
The class D carbapenemase OXA-48 was first detected in 2001 from a carbapenem-resistant Klebsiella pneumoniae isolate in Istanbul, Turkey [1]. The variant OXA-181, which differs from OXA-48 by four amino acids, was isolated later in India in 2007 from Enterobacter cloacae and K. pneumoniae. Since then, OXA-181 has been reported in Bangladesh, India, South Africa, Canada, France and New Zealand [2,3]. Here we report the first case of OXA-181-producing Escherichia coli identified in Lebanon.